Does Proprioceptive Impairment Affect Feedforward Motor Control? A Cross-Sectional Study on Patients With Brain Damage - Nicola Vale; Anna Righetti; Enrico Martini; Michele Boldo; Nicola Bombieri; Nicola Smania (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Sensory ataxia and cerebellar ataxia share common manifestations including dysmetria, intentional tremor and lack of smoothness. We formulated a theoretical framework to describe the patients’ sensory and cerebellar ataxic behavior as consequences of a forward model impairment. To test this framework, the present study aimed to compare upper limb movement kinematics in an index-to-nose task between three groups: healthy controls, people with CNS focal lesions and cerebellar deficits and people with CNS focal lesions and somatosensory impairment. We recruited 12 healthy controls (age $= 29.0± 2.9$ years, female = 5) and 20 participants with focal CNS lesions. We divided the sample according to the lesion site in participants with lesions in areas involved in the somatosensory information processing (n = 12, age $= 62.4± 13.6$ years, female = 5) and participants with lesions in the cerebellum or cerebellar peduncle (n = 8, age $= 64.3± 13.9$ years, female = 1). Movement features concerning movement efficiency (average velocity, peak velocity), accuracy (spatial error when pointing to the nose) and motor planning (timing and spatial occurrence of velocity peak, velocity and deviation from ideal trajectory at 150ms after the movement onset) were computed. Both the groups of participants with CNS lesions performed the movement slower than healthy controls. When comparing results from the two groups of patients, we showed that participants with cerebellar lesions were characterized by greater trial-to-trial variability of the velocity peak (repeated measure ANOVA group effect: F = 5.242, p = 0.012) and its timing (condition*group interaction: F = 5.38, p = 0.011). Our findings suggested that both participants with cerebellar and somatosensory deficits showed signs of anticipatory motor control impairment.